PENGARUH STRATEGI BISNIS DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP KUALITAS SISTEM INFORMASI AKUNTANSI MANAJEMEN (STUDI PADA PT LESTARI MAHAPUTRA BUANA) - Arti Muslimatunisa (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2018)
Business Strategy is a set of plans and integrated action which is designed for the company As a means to gain profit beyond its competitors As well as to maximize profit. Basically, Environmental Uncertainty is difficult to predict, the necessary information is a commodity that is very useful in the process of planning and control activities in an oranization so as to produce a system that is reliable accounting information management. This study aims to determine how business strategy, uncertainty of the environment and the quality of management accounting information system at PT. Lestari Mahaputra Buana and prove the influence of Business Strategy and Environmental Uncertainty on the Quality of Accounting Information System Management. The method used in this research is descriptive method with quantitative approach through data collection techniques with questionnaires distributed directly to all of management accounting system in PT. Lestari Mahaputra Buana in good categories. The results showed 1) There is a significant influence of business strategy on the quality of management accounting information systems. 2) environmental uncertainty significantly effects the quality of management accounting information systems.